2010
DOI: 10.1093/cercor/bhq040
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Infragranular and Supragranular Synaptic Input onto Layer 5 Pyramidal Neurons in a Rat Model of Cortical Dysplasia

Abstract: Cortical dysplasias frequently underlie neurodevelopmental disorders and epilepsy. Rats with a neonatally induced cortical microgyrus [freeze-lesion (FL)], a model of human polymicrogyria, display epileptiform discharges in vitro. We probed excitatory and inhibitory connectivity onto neocortical pyramidal neurons in layers 2/3 and 5 of postnatal day 16-22 rats, approximately 1-2 mm lateral of the lesion, using laser scanning photostimulation (LSPS)/glutamate uncaging. Excitatory input from deep and supragranul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Increased synaptically-evoked TC amplitude and unchanged uncaging-evoked TC amplitude together suggest that there are changes in endogenous glutamate release rather than astrocyte glutamate uptake. In line with this hypothesis, the threshold to evoke a synaptic TC was significantly lower in the FL cortex, indicating that neuronal glutamatergic inputs are increased in number or that ascending axons are more easily activated (Brill and Huguenard, 2010; Dulla et al, 2012; Jacobs et al, 1999c). The delayed onset of synaptically-evoked TCs in the microgyrus also supports a model of FL pathology which includes large-scale reorganization of afferent excitatory fibers (Jacobs et al, 1999b; Jacobs et al, 1999c).…”
Section: Discussionsupporting
confidence: 59%
“…Increased synaptically-evoked TC amplitude and unchanged uncaging-evoked TC amplitude together suggest that there are changes in endogenous glutamate release rather than astrocyte glutamate uptake. In line with this hypothesis, the threshold to evoke a synaptic TC was significantly lower in the FL cortex, indicating that neuronal glutamatergic inputs are increased in number or that ascending axons are more easily activated (Brill and Huguenard, 2010; Dulla et al, 2012; Jacobs et al, 1999c). The delayed onset of synaptically-evoked TCs in the microgyrus also supports a model of FL pathology which includes large-scale reorganization of afferent excitatory fibers (Jacobs et al, 1999b; Jacobs et al, 1999c).…”
Section: Discussionsupporting
confidence: 59%
“…Surprisingly, the age of onset for increased susceptibility does not match the timing of one of the previously identified potential epileptogenic mechanisms, that of increased excitatory afferents to layer V pyramidal neurons (Zsombok and Jacobs, 2007). We have also suggested that alterations occur in specific interneuron subtypes (George and Jacobs, 2006; George and Jacobs, 2011), and some effects on interneurons suggest anti-epileptogenic effects (Brill and Huguenard, 2010; Jacobs and Prince, 2005). Yet to be determined is the onset timing for these pro and anti-epileptogenic interneuron effects.…”
Section: Discussionmentioning
confidence: 91%
“…For example, in the isolated cortical slab, which produces epileptogenic insult (Fig. 5a), enhanced connectivity was restricted to infragranular layers, especially layer 5 93 ; however, in a model of focal cortical dysplasia, enhanced connectivity to layer 5 cells was seen from both infra and supra-granular regions 94 . These findings suggest that lesion-specific reorganization occurs in different injury models.…”
Section: Recurrent Excitationmentioning
confidence: 99%